Islamic Studies in Germany A cultural bridge between Ost and West - Rasha Zenhom; Mohammed Abdelrahem (Journal of Architecture, Art & Humanistic Science, 2021)
One of the largest and oldest factors in the convergence of cultural thought between East and West in general, and between the West and Islam in particular, is the factor of academic studies that have touched Islamic studies, Islamic civilization and the Arabic language and its characteristics in the West. Universities since the seventeenth century. From now on, the term "Orientalism" has emerged. The goals and contents of the Orientalist studies were varied, and so were the tours of Western travelers in our Islamic world. One of their most important goals was to pave the way for colonization and proselytism. Some of these goals ultimately served Arab and Islamic cultural heritage through scholarly debates, some of which were fair and equitable, others were abusive and arbitrary.Orientalism has long been characterized by East-West relations for centuries, during which many stereotypes of the East have emerged. Perhaps the most important criticism of this science is what the writer and thinker Edward Said mentioned in his famous book Orientalism, where he analyzed how the West "makes" the idea of ​​the East as a fixed and unchanging identity. When Edward Said wrote about Orientalism, he points to the balance of power that existed in the past between colonial West and colonial East. He sees that the West was dominant and superior, and determined the directions and topics of studies, while the East was preoccupied with resisting the West politically instead of studying it. So, for example, there was no equivalent science through which the East could study the West - that is, the "West" - as if the East had realized that the WestIt cannot be simplified to such an extent. Dr. Rudi Barrett posed the same question in his book on Arab-Islamic Studies and asked if Muslims in the present era can study the West.